Synthesis and characterization of Fe(III)-doped ceramic membranes of titanium dioxide and its application in photoelectrocatalysis of a textile dye - Rodrigues, Emanuel Carlos; Soares, Layciane Aparecida; Modenes Junior, Marco Antonio; de Sene, Jeosadaque José; Bannach, Gilbert; de Carvalho, Claudio Teodoro; Ionashiro, Massao (Eclética Química, 2011)
Pure and Fe(III)-doped TiO2 suspensions were prepared by the sol gel method with the use of titanium isopropoxide (Ti(OPri)4) as precursor material. The properties of doped materials were compared to TiO2 properties based on the characterization by thermal analysis (TG-DTA and DSC), X-ray powder diffractometry and spectroscopy measurements (FTIR). Both undoped and doped TiO2 suspensions were used to coat metallic substrate as a mean to make thin-film electrodes. Thermal treatment of the precursors at 400°C for 2 h in air resulted in the formation of nanocrystalline anatase TiO2. The thin-film electrodes were tested with respect to their photocatalytic performance for degradation of a textile dye in aqueous solution. The plain TiO2 remains as the best catalyst at the conditions used in this report.